Colombia : the Bradt travel guide - Woods, Sarah (Chalfont St. Peter, Bucks, England : Bradt Travel Guides ; Guilford, Conn. : Globe Pequot Press, 2008)
A comprehensive travel guide to Colombia, with maps and information on accommodations and restaurants, shopping and entertainment, and interesting tourist sites.
Includes bibliographical references (p. 432-439) and index.
Adult
Adult
Keywords: Colombia -- Guidebooks; Colombia -- Guidebooks